Music therapy effect on anxiety reduction among patients with cancer: A meta-analysis - Zang, Lu; Cheng, Chunliang; Zhou, Yongxin; Liu, Xuemei (Frontiers in Psychology, 2023)
The study aimed to investigate the effect of music therapy on anxiety alleviation among cancer patients. A comprehensive literature research was performed in four electronic databases (PubMed, Embase, Cochrane Library, and Web of Science). Fifteen randomized controlled trials (RCTs) were included. The risk of bias for the RCTs was evaluated by the Cochrane Risk of Bias tool. Anxiety levels were extracted to synthesize the combined effect by using meta-analysis. All analyses were performed using R version 4.0.4. In total, 15 RCTs met the inclusion criteria involving 1320 cancer patients (662 patients in the experimental group and 658 patients in the controlled group). The majority of interventions were performed with recorded music lasting for 15-60 minutes. Compared with standard care, music intervention had a moderate superiority of anxiety alleviation (SMD: -0.54, 95% CI: [ -0.92, -0.61]). Music intervention could reduce cancer-related anxiety moderately. Nevertheless, the result should be interpreted with caution as high heterogeneity in this pooled study. Well-designed trials with higher quality were still warranted in the future.